APPLICATION OF WEBBED BASED WORKSHEET TO IMPROVE STUDENT SCIENCE PROCESS SKILLS - Sofi Novita Ramadhani; Enny Susiyawati (PENDIDIKAN SAINS DAN TEKNOLOGI, 2024)
Abstract: This study aims to examine the applicatio of webbed based worksheet to improve student science process skills. This study used a one-group pretest and posttest pre-experimental research design. 26 students in class VIII-D participated in this study from 39 JHS in Surabaya. Datas were collected through teaching activity, science process skill pretest-posttest, and students’ responses. The collected teaching activity was calculated using modus, the improvement of SPS was analyzed using n-gain value and students’ responses will be shown by percentage. The result of study was shown an improvement in the observations of how the learning was being put into practice, with modus 3 in good categoty. The N-Gain result was 0.73 on high category to demonstrated students' science process skills development from the result pretest posttest. The webbed based worksheet on human skin health received a positive responses from students, with a percentage of 95% on very good category. The result indicated that the application on webbed based worksheet can improved students’ science process skills on skin health theme. Keywords: Webbed type, Student Process Skills